Russia-Ukraine Crisis And Economic Sanction: Power Politics Through Geoeconomic Means - Kumar, Dharmendra (Shanti Journal, 2022)
The nature of international politics has always been volatile, chaotic and anarchic. The state’s national interest remains permanent when dealing with others. Although the current Russian invasion of Ukraine has been driven by the national interests objective and forthcoming security threat from North Atlantic Treaty Organisation (NATO). Ukraine’s wish to join NATO is the ultimate cause of War. Now, military escalation has taken place and this war has created the largest humanitarian crisis Europe has seen in decades. The war also leads to the global crisis in rising oil and gas prices, and food stuff shortages. Now, the Eurasian region has become a hotbed of power struggles between the Western bloc and Russia. However, Western countries placed a series of sanctions on Russia in response to the invasion, aimed at weakening its economy. Despite this, most European countries still purchase Russian oil and gas. As a result, it has become ambiguous due to geopolitical and geoeconomic interplay in the ongoing war. On the other hand, Ukraine is also receiving military aid from western countries to fight Russia. So, this paper will discuss the current crisis via a geoeconomic lens, as well as how power politics is played through geoeconomic methods.